Is the Incidence of Gastroschisis Increasing Recently? - Aditya Pratap Singh; Arun Kumar Gupta; Ramesh Tanger; Vinay Mathur; Dileep Garg (EL-Med-Pub, 2018)
Aims and Objectives: Gastroschisis is a predominantly full thickness right-sided periumbilical abdominal wall defect. We have observed that the GS birth prevalence has more than doubled over the past few decades. The aim of our study is to point out the increasing incidence of the GS. Materials and Methods: We conducted a retrospective study to collect data of the GS, admitted in our institute during the period of 2 years from January 2015 to December 2016. The very high incidence of this congenital anomalies together with the fact that GS is the most common abdominal wall defect requiring neonatal operative intervention and its mortality rate is still very high that prompted us to study its demography, descriptive epidemiology, and quantifying mortality rate and try to analyze factors affecting outcome and cause that might explain this epidemiological pattern. Low- and middle-income countries are often reported to have a higher mortality when compared to patients born in the developed countries. Results: A total of 98 patients of the GS were admitted during the period of 2 years. The mortality and survival rate were 26.5% (26) and mortality 73.4% (72) respectively. Conclusion: Our data demonstrate that in our institution too, recent trends of increasing prevalence of GS are real. Still, we had a high mortality rate. This study highlights the need for further research to find out the causes of such high incidence rates and to improve our outcomes.